A lightweight write-assist scheme for reduced RRAM variability and power. (September 2018) - Aziza, H.; Hajri, B.; Mansour, M.; Chehab, A.; Perez, A.
Abstract: Common problems with Oxide-based Resistive RAM are related to high variability in operating conditions and high programming currents during FORMING, SET and RESET operations. Although research has taken steps to resolve these issues, variability combined with high programming currents remains an important characteristic for RRAMs. In a conventional write scheme with fixed duration and amplitude, the programming current is not controlled, which degrades the cell performance (power consumption and variability) due to over-programming. In this paper, a self-adaptive write driver is proposed to control the write current. A feedback mechanism based on current comparison is used to switch off the write stimulus as soon as the preferred write current is reached. Compared to conventional write schemes, in the proposed write-assist circuit, the write energy per bit is reduced by 27% and the standard deviation of post-FORMING distributions is reduced by 57%.